Malpighiaceae from the Reserva Biológica da Mata Escura, Minas Gerais, Brazil - de Almeida, Rafael Felipe (Heringeriana, 2021)
I present the taxonomic treatment for Malpighiaceae Juss. (Malpighiales) from the Reserva Biológica da Mata Escura (RBME), Minas Gerais, Brazil, in which a total of 17 species and eight genera were recorded. Identification keys for all genera and species are presented, alongside photo plates, and comments on distribution, ecology, and taxonomy of the studied species.